Environmentally friendly food in Malaysia: an overview - Mohamed Zain, Izzah Nadhirah; Abdul Rahman, Haliza; Ezani, Nor Eliani; Mohd Norowi, Noris (Human Resource Management Academic Research Society, 2024)
Humans require healthy and high-quality foods to obtain adequate nutrition to lead a better life. Food consumption has a substantial environmental impact since it emits greenhouse gases, which cause global warming and climate change. A shift in consumer behavior towards sustainable foods could be a more practical strategy to significantly reduce this impact. Therefore, the objective of this study is to ascertain the current status of Malaysians' food preferences and the factors that contribute to the consumption of environmentally friendly food in Malaysia. The articles selected for this study were obtained from sources like PubMed, Scopus, Science Direct, and Google Scholar that focus on Malaysia's sustainable food consumption over five years, from 2020 to 2024. This review showed that the majority of Malaysians have a low consumption of fruits and vegetables. Race, age, and economic background are sociodemographic factors, whereas habits and lifestyles, such as health concerns, are personal factors that have a substantial impact on Malaysians' purchase of environmentally friendly food. In conclusion, the concept of environmentally friendly food can help ensure that the selected foods are safer, have minimal impact on the environment, and are expected to foster a healthier lifestyle for current and future generations in Malaysia.